ANALISIS AUTOKORELASI SPASIAL KEMISKINAN DI PROVINSI SUMATERA BARAT - monsaputra, monsaputra (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2022)
Spatial autocorrelation has used to obtain information on the distribution pattern and the interrelationships between locations. One indicator of welfare is the level of poverty. West Sumatra has resource potential, but it has not been fully utilized, so the poverty rate is still high. Maximizing sectors that have a comparative advantage is a strategy to reduce poverty. This study aims to determine analyze the spatial pattern of poverty and analyze sectors that have a comparative advantage. The  methods of this study is the Moran Index, LISA and LQ. The results of the Moran index analysis show that there is no spatial autocorrelation of poverty, while LISA shows that there is a local spatial autocorrelation in the Mentawai Islands District. Regions that have an average percentage of the poverty rate above the percentage of the province have a comparative advantage in the agriculture, forestry and fisheries sectors. Keywords : compartive, spatial autocorrelation, poverty